Implementation of Monitoring, Evaluation and Supervision for More Quality Social Service in the System of Social Protection of the Republic of Macedonia - Nackovska – Veljkovikj, Biljana (European Journal of Multidisciplinary Studies, 2016)
The need for implementation of monitoring, evaluation and supervision in the system of social protection, in fact, stems from the need to modernise the organisation and work methodology of the providers. Service providers are often required or given support in developing ways to monitor the services provided (monitoring) and in the assessment and evaluation of the results of those services (evaluation). Supervision focuses on the fact how the work is done to quantitatively and qualitatively acceptable level. The following have been defined as research priorities in this area: the impact of monitoring, evaluation and supervision for better social service and determining the status for their application in institutions of social protection in the Republic of Macedonia. This paper explains its three components (areas): monitoring, evaluation and supervision in the social work. The objectives of their implementation are the welfare of the beneficiary, improving the quality of work and professional development of professional workers through the preservation and development of professional standards and the standards of a given service.